The estimation of the viable count of mutans streptococcus in waterpipe smokers and cigarette smokers - Fathallh , Ausama A; Mahmood , Maha A (Journal of Baghdad College of Dentistry, 2021)
Background: Waterpipe and cigarette are two products of tobacco consumption, tobacco use has detrimental effects on the oral cavity, numerous studies around the world have reported a significant relationship between smoking and increase dental caries and viable count of cariogenic bacteria, Materials and Methods: unstimulated saliva was collected from 84 subjects and divided equally into three groups waterpipe smokers, cigarette smokers, and non-smokers all of the participants are adult male aged between 25-60 years, dental caries was measured by use DMFT index, while S.mutans and S.sobrinus were isolated by using a selective medium SB 20M (Sugar bacitracin-20 modified) agar Results: this present study showed a significant (p≤0.01). higher DMFT, DT, MT, and FT among cigarette smokers group than both waterpipe smokers and non-smokers groups. The viable count of S mutans was significantly (p≤0.01).higher in the cigarette smokers group followed by the waterpipe smokers group and then the non-smoker's group, while the viable count of S sobrinus showed no statistical differences (P>0.05) between groups. The correlation of DMFT with S.mutans, and S sobrinus count, were significantly positive (p ≤0.05), in the cigarette smokers group only Conclusion: Dental caries increase in cigarette smokers, where the DMFT and S mutans viable count are less affected by waterpipe than cigarette smoking, a positive correlation is found between DMFT and .mutans streptococcus count only in cigarette smokers